the MANFAAT RENDAM KAKI DENGAN AIR HANGAT DAN SERAI TERHADAP TEKANAN DARAH IBU BERSALIN: Blood pressure, maternity, foot soaking, warm water, lemongrass - Durrotun Munafiah; Dwi Sulistiyowati; Sheilla Aniendhita; Novita Sari (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2026)
The labor process represents a critical phase in the life cycle. One of the prevalent issues that frequently emerge during this phase is the fluctuation of blood pressure. Primary aim of this investigation is to ascertain the influence of immersing feet in warm water infused with lemongrass on the reduction of blood pressure in parturient mothers at the Manyaran Community Health Center, located in Semarang City. This study employed a quasi-experimental research design featuring a single-group pretest and posttest framework without a control group. A total sample of 32 parturient mothers who fulfilled the inclusion criteria was selected through total sampling methodology. The instrument utilized for data collection was a blood pressure observation sheet administered prior to and following the intervention. Data analysis was conducted utilizing descriptive statistics and Paired T-tests. Following the intervention, a notable decrease in systolic blood pressure was observed, with the mean declining from 137.65 mmHg to 93.13 mmHg, and diastolic blood pressure reducing from 123.59 mmHg to 81.09 mmHg. The outcomes of the Paired T-test yielded a p-value of 0.000 for both blood pressure parameters (p < 0.05), indicating a statistically significant effect on the reduction of maternal blood pressure subsequent to immersion of the feet in warm water and lemongrass. It can be inferred that the practice of soaking feet in warm water combined with lemongrass serves as an effective, straightforward, safe, and economically viable non-pharmacological intervention for the attenuation of blood pressure in mothers prior to childbirth.